WORK-RELATED EMOTIONAL EXHAUSTION AND ITS MANIFESTATIONS (American Journal of Interdisciplinary Research and Development, 2024)
The article contains information about work-related emotional fatigue and its manifestations, burnout syndrome, views of scientists, psychological diseases that can be caused by fatigue as a complication of work-related problems.